Odpowiedź :
P(x,y)=( 1/2 )xy i x+y=m y=m-x
P(x)=(1/2)x(m-x)
P(x)=( -1/2)x^2+(1/2)mx
x=(-1/2)m/(-1) stąd x=(1/2)m
y=m-x i x=(1/2)
y=(1/2)m
x=(1/2)m i y=(1/2)m
P(x)=(1/2)x(m-x)
P(x)=( -1/2)x^2+(1/2)mx
x=(-1/2)m/(-1) stąd x=(1/2)m
y=m-x i x=(1/2)
y=(1/2)m
x=(1/2)m i y=(1/2)m
a - długość podstawy trójkąta
h - długość wysokości opuszczonej na tę podstawę
P(a,h)=½ah
a+h=m
h=m-a
P(a)=½a(m-a)
P(a)=-½a^2+½am
a=-½m/(-1)
a=½m
h=m-a
a=½m
h=½m
h - długość wysokości opuszczonej na tę podstawę
P(a,h)=½ah
a+h=m
h=m-a
P(a)=½a(m-a)
P(a)=-½a^2+½am
a=-½m/(-1)
a=½m
h=m-a
a=½m
h=½m